Cytotoxic Constituents from the Rhizomes of Curcuma zedoaria. (10th July 2014) - Ahmed Hamdi, Omer Abdalla; Syed Abdul Rahman, Syarifah Nur; Awang, Khalijah; Abdul Wahab, Norhanom; Looi, Chung Yeng; Thomas, Noel Francis; Abd Malek, Sri Nurestri
Abstract : Curcuma zedoaria also known as Temu putih is traditionally used in food preparations and treatment of various ailments including cancer. The cytotoxic activity of hexane, dichloromethane, ethyl acetate, methanol, and the methanol-soxhlet extracts of Curcuma zedoaria rhizomes was tested on two human cancer cell lines (Ca Ski and MCF-7) and a noncancer cell line (HUVEC) using MTT assay. Investigation on the chemical components in the hexane and dichloromethane fractions gave 19 compounds, namely, labda-8(17), 12 diene-15, 16 dial (1 ), dehydrocurdione (2 ), curcumenone (3 ), comosone II (4 ), curcumenol (5 ), procurcumenol (6 ), germacrone (7 ), zerumbone epoxide (8 ), zederone (9 ), 9-isopropylidene-2, 6-dimethyl-11-oxatricyclo[6.2.1.0 1, 5 ]undec-6-en-8-ol (10 ), furanodiene (11 ), germacrone-4, 5-epoxide (12 ), calcaratarin A (13 ), isoprocurcumenol (14 ), germacrone-1, 10-epoxide (15 ), zerumin A (16 ), curcumanolide A (17 ), curcuzedoalide (18 ), and gweicurculactone (19 ). Compounds (1 –19 ) were evaluated for their antiproliferative effect using MTT assay against four cancer cell lines (Ca Ski, MCF-7, PC-3, and HT-29). Curcumenone (3 ) and curcumenol (5 ) displayed strong antiproliferative activity (IC 50 = 8.3 ± 1.0 and 9.3 ± 0.3   μ g/mL, resp.) and were found to induce apoptotic cell death on MCF-7 cells using phase contrast and Hoechst 33342/PI double-staining assay. Thus, the present study provides basis for the ethnomedical application of Curcuma zedoaria in the treatment of breast cancer.